Exploring Nurses' Knowledge and Experiences Related to Trauma-Informed Care. (6th October 2017) - Stokes, Yehudis; Jacob, Jean-Daniel; Gifford, Wendy; Squires, Janet; Vandyk, Amanda
Trauma-informed care is an emerging concept that acknowledges the lasting effects of trauma. Nurses are uniquely positioned to play an integral role in the advancement of trauma-informed care. However, knowledge related to trauma-informed care in nursing practice remains limited. The purpose of this article is to present the results of a qualitative study which explored nurses' understandings and experiences related to trauma-informed care. Seven semistructured interviews were conducted with nurses and four categories emerged from the analysis: (a) Conceptualizing Trauma and Trauma-Informed Care, (b) Nursing Care and Trauma, (c) Context of Trauma-Informed Care, and (d) Dynamics of the Nurse–Patient Relationship in the Face of Trauma. These findings highlight important considerations for trauma-informed care including the complex dynamics of trauma that affect care, the need to push knowledge about trauma beyond mental health care, and noteworthy parallels between nursing care and trauma-informed care.